Reviewing The Role of Gratitude on Student Life Satisfaction in Yogyakarta - Mujidin, Mujidin; Rustam, Husnul Khotimah; Nabilah, Syadza (Universitas Nahdatul Ulama Surabaya, 2024)
Students began to feel unhappiness and dissatisfaction in their lives. Students needed solutions to stabilize their dissatisfaction so that students could develop their potential and abilities optimally. Therefore, the purpose of this study was to determine the optimization of student satisfaction with the effect of gratitude. The total sample was found 80 students at University X. The findings of this study indicated that student satisfaction could be optimal with the influence of gratitude. The effect of gratitude on student satisfaction was 0.862. The effective contribution of gratitude is 74.3% so that it can be concluded that gratitude could strengthen students' life satisfaction in the past, present, future and the assessment of their lives was also positive. With a lot of gratitude, students were able to feel positive energies from the many pressures that came around them. Students were able to adapt and solve problems through appropriate coping strategies such as strengthening empathy, self-control, being grateful and not forcing their wilingnessl or opinions. Students with satisfied characteristics were easier to optimize their potential and abilities, even greater when they were passionate about what they were doing. This research can be recommended for further researchers, either with student satisfaction or other factors that affected student satisfaction